Exploring the role of peer observation of teaching in facilitating cross-institutional professional conversations about teaching and learning. Issue 3 (3rd July 2021) - O'Keeffe, Muireann; Crehan, Martina; Munro, Morag; Logan, Anna; Farrell, Ann Marie; Clarke, Eric; Flood, Michelle; Ward, Monica; Andreeva, Tatiana; Van Egeraat, Chris; Heaney, Frances; Curran, Declan; et al.
ABSTRACT: This paper explores how cross-institutional Peer Observation of Teaching (PoT) provided a stru ctured opportunity for professional conversations by which observers and observees shared and developed their perspectives on teaching experience and skills. Such professional conversations offer opportunities for both parties to gain a perspective on practices that may have been taken for granted. Participants from three Higher Education institutions engaged in cross-disciplinary and cross-institutional PoT, followed by facilitated reflective conversations. This paper captures the factors for success that enabled continuing conversations on teaching and learning and highlights the value of supporting such conversations outside formal, uni-institutional peer observation programmes.